Implementasi Pengembangan Sistem Informasi Laporan Bayi Baru Lahir Menggunakan Metode Agile Guna Menunjang Penerbitan Surat Keterangan Neonatus - Ningrum, Yushinta Lutfiya; Setyawan, Adhita Arif; Suryani, Ade Irma (Program Studi Teknik Informatika Universitas Pamulang, 2024)
The hospital is now in the process of transitioning to the application of electronic medical records, so the production of neonatal registration forms at the hospital is still paper-based. The aim of this program is to make it easier for officers to make neonatal records at the Kebonjati Hospital so that they can use the electronic system more quickly. Thel research method thatl will ble used bly the rlesearchers isl qualitative. The process of data collection through the observation and interview results techniques and in the design techniques the author uses Agile Development Methods. The author also designed an information system through the Visual Studio Application in the system designer that the author would develop. With this design, the system gets more accurate data and can minimize errors or incompleteness of baby data. Of course there is a reason the author has that underpins this research, the author raises this title based on observations during the Field Work Practice, the writer identifies a common problem where neonate registration letters are still not electronically available and a lot of incomplete data in the Neonate Registration Forms. Therefore, the author concluded that